An assessment of the availability of selected teaching-learning materials in primary schools in Abia State, Nigeria (2009)
This study investigated the extent to which primary schools, as part of basic education, have some teaching-learning materials in Abia State. The sample comprised of 165 head teachers selected by stratified random sampling from five different categories of schools in the 17 local government areas in the state. The results indicate that the availability, condition and adequacy of some teaching-learning materials ranged from 19.7% (for Pupils' Mathematics Textbook) to 115.1% (for Teachers' Mathematics Textbook) for availability: 78.1% (for Curriculum Modules) to 97.7% (for Schemes of Work/Diaries) for conditions; and 20.6% (for teachers' Guide in English) to 66.7% ( for Schemes of Work/Diaries) for adequacy of the teaching-learning materials, respectively. These results revealed that many primary schools are not child-friendly in terms of teaching-learning materials.